Prevalence of cutipositivity in a sample of homeless shelter population in Rome in the course of Latent Tuberculosis Infection surveillance plan. Preliminary results (Italian Journal of Public Health, 2010)
Background: in Europe homelessness is a known risk factor both for active and latent tuberculosis (TB). InRome 409 cases of TB were notified in 2004, but the real occurrence among homeless people is unknown.Tuberculosis surveillance has been organized with the aim to develop an integrated model for the riskevaluation and management of both Latent Tuberculosis infections (LTBI) and TB in Rome homeless people.Methods: the eligible individuals have been recruited in the homeless’ refuges. The Tuberculin Mantoux testhas been used to evaluate the infection prevalence; in case of a positive result, the individual’s expectoratehas been collected and the chest X-ray has been performed. A collecting data form has been filled in forevaluating some risk factors. Multiple logistic regression models have been carried out to find statisticallysignificant determinants of infection.Results: out of 120 subjects recruited, 108 came back for the evaluation of the skin test; the prevalence ofLTBI was 43.5% (47/108 subjects); no active TB cases were found. According to the multivariate analysis,factors significantly associated to LTBI are gender (for males OR = 4.94; 95% CI: 1.46 – 16.67, 1st model; OR5.84; 95% CI: 1.26 – 21.10, 2nd model), birth place (for Europe: OR 3.05; 95% CI: 1.02 – 9.13, 1st model; OR3.12; 95% CI: 1.10 – 8.88, 2nd model; for East Mediterranean native Region OR = 4.34; 95%CI: 1.15-16.39);Body Mass Index class (for obesity OR = 3.34; 95% CI:1.31-8.51).Conclusions: these preliminary results have demonstrated a high prevalence of LTBI among homeless people.Male gender, birth place (Europe and East Mediterranean native Region) and obesity were found to besignificant risk factors. The surveillance system allowed positive patients for LTBI to be rapidly directed to aspecialized centre for the clinical evaluation and the appropriate therapy in order to prevent the evolution ofdisease.
Keywords: homeless; Italy; Latent Tuberculosis infections; surveillance; tuberculosis